(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Given its complexity and dynamic nature, the construction sector is beginning to understand how important it is to have efficient information management in order to improve sustainability practices. This study aims to examine the challenges that information management faces in the course of advancing sustainability in the South African construction industry. With the use of structured questionnaires, data were gathered quantitatively from 209 experts, including project managers, engineers, and architects. The study employed mean item scores and exploratory factor analysis (EFA) to identify crucial elements influencing the implementation of information management systems in construction projects. The findings revealed three primary challenges to effective information management which include technical factors, human factors, and legal and security issues. The results provide valuable insights for industry stakeholders, offering guidance on addressing these challenges to achieve more sustainable construction practices.